The Electronic Structure of NiO by means of Electron Spectroscopies and theoretical calculations - Soriano de Arpe, Leonardo (APS, 2007)
We report experimental and theoretical evidence of surface effects in the Ni 2p x-ray photoemission spectra XPS of NiO. The Ni 2p3/2 surface-enhanced XPS of a NiO sample show a relative enhancement of the intensity of the known satellite at 1.5 eV higher binding energy from the main line, indicating a considerable surface contribution of this satellite. The results are discussed in terms of bulk-octahedral and surfacepyramidal Ni symmetries. Other contributions, like nonlocal screening effects, cannot be neglected.
Keywords: Fotoemisión; Física; Photoemission; NiO/oxide interface